Advancements and Challenges in Multidomain Multicargo Delivery Vehicles. Issue 13 (15th February 2018) - Pugliese, Eugenia; Coentro, João Q.; Zeugolis, Dimitrios I.
Abstract: Reparative and regenerative processes are well‐orchestrated temporal and spatial events that are governed by multiple cells, molecules, signaling pathways, and interactions thereof. Yet again, currently available implantable devices fail largely to recapitulate nature's complexity and sophistication in this regard. Herein, success stories and challenges in the field of layer‐by‐layer, composite, self‐assembly, and core–shell technologies are discussed for the development of multidomain/multicargo delivery vehicles. Abstract : Reparative and regenerative processes are well‐orchestrated temporal and spatial events that are governed by multiple cells, molecules, signaling pathways, and interactions thereof. Currently available single‐cargo‐delivery vehicles fail to recapitulate nature's complexity and sophistication. Advancements and challenges in the field of layer‐by‐layer, self‐assembly, composite, and core–shell technologies are discussed for the development of multidomain/multicargo delivery vehicles.